On the inverse design of discontinuous abrasive surface to lower friction-induced temperature in grinding: an example of engineered abrasive tools - Li, Hao Nan; Axinte, Dragos (Elsevier, 2018)
In order to lower temperature, abrasive tools with passive-grinding, e.g. textured, areas (PGA) have been suggested. However, most of the reported PGA geometries (e.g. slots, holes) have been determined based on the engineering intuition (i.e. trial and error) rather than in-depth phenomenological analysis. To fill this gap, this paper proposes a method to design the PGA geometry according to the desired temperature, i.e. the inverse design method. In the method, the analytical model of grinding temperature for tools with PGA is established and treated as the primary constraint in the inverse problem, while the models of the ground surface roughness and grinding continuity as the subsidiary constraints. The method accuracy is validated by conducting grinding trials with tools with the calculated PGA geometries and comparing their performances (temperature, roughness and force fluctuation) to the required ones. In comparison with conventional tools, our tools designed by the method have been found effective to reduce harmful, or even destructive, thermal effects on the ground surfaces. This work might lay foundation for designing discontinuous abrasive tools, and future work can be probably extended to the tools or the workpiece with more complex shapes (e.g. ball end/cup tools, and free-form workpiece).